PKM Pengembangan Usaha IRT Bunga Telang Di Desa Pemecutan Denpasar - Ni Wayan Cahya Ayu Pratami; Ni Nyoman Muryatini; Ni Kadek Sukerti; Ni Made Dwijayani; A. A. Ayu Meitridwiastiti; I Gst Bagus Agung Kusuma Atmaja; Ni Putu Linda Santiari; I Gede Surya Rahayuda; I Gede Satria Wibawa; Komang Bhargo Bhaskara (STIKOM Bali, 2021)
Bunga Telang (Asian Pigeonwings) is one of vine flowers commonly found in the yard. Bunga Telang has many benefits, especially for health such as increasing stamina, works as antioxidant, improving memory, improving heart health, reducing inflammation and etc. In Bali, Bunga Telang is usually used in rituals of worshipping gods and goddesses. The university dedication partner, I Nyoman Ariadi Putra, seized the opportunity to take advantage of the benefits of Bunga Telang for health. I Nyoman Ariadi Putra mixed this flower into herbal drink for health, especially during the Covid pandemic. This home industry which is located in Pemecutan Kaja Village, Denpasar, has only been running since the beginning of the Covid outbreak in Indonesia. The ingredients used are dried Bunga Telang, lemon, ginger, and sugar. Obstacles found in the field are that the production managements have not been optimal yet, such as the manual drying process and the limited tools. Therefore, it is considered not optimal in terms of production. Furthermore, the products have not been lebelled. Hence, this dedication program was conducted to assist this home industry to improve the quality and the quantity of its products so it can increase its income. The method used was providing production tools and then providing counseling, labelling and online marketing media training.